Ecosystem services of headwater catchments - Křeček, Josef; Haigh, Martin J., 1950-; Hofer, Thomas, 1960 June 13-; Kubin, Eero; Promper, Catrin (Springer, 2017)
This book addresses the evaluation of environmental impacts and services identified in headwaters of different eco-zones around the world. It presents 24 papers selected from contributions to recent meetings of the European Forestry Commission Working Party on the Management of Mountain Watersheds, which is coordinated by the FAO (Food and Agriculture Organization of the United Nations). Through its biennial sessions and inter-session activities, the Working Party focuses on the continuous exchange of knowledge and experience between professionals in Europe and other regions of the world confronted with similar issues. The contributions have been updated and peer-reviewed, and the interdisciplinary team of authors includes experts from the fields of geography, hydrology, chemistry, biology, forestry, ecology and socio-economics. The participatory management of headwater catchments in Europe, Africa, America and Asia was the central theme of the articles, which were divided into four sessions: (1) Headwater Environment and Natural Resources, (2) Enhancing Environmental Services in Headwaters, (3) Environmental Services in the Changing World, and (4) New Challenges for Environmental Education and Active Citizenship. The practical applications shown in the book address the multi-resource concept. The book offers a unique and valuable resource for environmentalists, engineers, watershed planners and policymakers alike.